Lung cancer, predictive factor and ERCC1 - Souilah, Souad (International Journal of Medicine, 2024)
Introduction: Excision repair cross-complementing group 1 (ERCC1) counteracts the cytotoxic effect of cisplatin through its role in DNA repair, and its expression level is a crucial factor for sensitivity to this drug. The objective of this study was to assess the impact of ERCC1 on tumor response and survival in patients with advanced non-small cell lung cancer (NSCLC) treated with a platinum-based regimen.Methods: Analysis of survival and tumor response based on the expression level of ERCC1 (detected by immunohistochemistry) in a cohort of NSCLC patients followed in a standard care setting.Results: Among the 77 cases of NSCLC included, ERCC1 expression was low in 64.9% of cases and high in 35.1% of cases. In the 52 patients treated with cisplatin, survival and tumor response were better in the low-expression group compared to the high-expression group: 14.35 months versus 9.49 months, p=0.022; Objective Response: 42.4% versus 0%, p=0.001. No significant difference was found based on protein expression level in patients treated with carboplatin.Conclusion: ERCC1 overexpression in patients treated with cisplatin predicts a poor tumor response and shorter survival.